FROM THE ARCHIVES OF LEVON MKRTCHYAN: Andrei Bitov at the Department of Russian Literature of the Yerevan State University, 1985 - SAHAKYANC, KARINE (Bulletin of Yerevan University H: Russian Philology, 2019)
The present paper, dedicated to the memory of Andrei Bitov, is a continuation of the first publication (see N1, 2019, pp.19-43). L. Mkrtchyan’s diary entries presented in the introductory note to this publication, as well as other details of the published text highlight the noteworthy fact of the biography and creative work of the outstanding Russian writer ( Bitov’s attempt supported by Mkrtchyan’s initiative to defend his text about Pushkin as a PhD thesis at the YSU), also reflecting the ingenious and friendly nature, style and creative level of his relations with Armenian colleagues.
Keywords: Bitov, Mkrtchyan, Yerevan University, Pushkin, disertation, discussion